Analyzing Fcγ-Receptor Interactions on Monocytes with the Proximity Ligation Assay (PLA) - Kara, Sibel; Nimmerjahn, Falk (Methods in Molecular Biology, 2024)
Proximity ligation assays (PLA) enable the detection and characterization of protein interactions independent of protein abundance or genetic modifications. This technique exploits both antibody and DNA-binding features, providing high selectivity and sensitivity for protein recognition and visualization of single-protein molecules with high spatial accuracy. Here, we describe the general procedure for a direct PLA on splenic monocytes to analyze FcγRIIb homodimerization. However, this method can be applied to other cells and receptors of interest.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Antibody; Fc receptor; Microscopy; Protein interaction; Proximity ligation assay (PLA)

Complement-Dependent Activity of CD20-Specific IgG Correlates With Bivalent Antigen Binding and C1q Binding Strength - Bondza, Sina; Marosán, Anita; Kara, Sibel; Lösing, Josephine; Peipp, Matthias; Nimmerjahn, Falk; Buijs, Jos; Lux, Anja (Frontiers in Immunology, 2021)
Monoclonal antibodies directed against the CD20 surface antigen on B cells are widely used in the therapy of B cell malignancies. Upon administration, the antibodies bind to CD20 expressing B cells and induce their depletion via cell- and complement-dependent cytotoxicity or by induction of direct cell killing. The three antibodies currently most often used in the clinic are Rituximab (RTX), Ofatumumab (OFA) and Obinutuzumab (OBI). Even though these antibodies are all of the human IgG1 subclass, they have previously been described to vary considerably in the effector functions involved in therapeutic B cell depletion, especially in regards to complement activation. Whereas OFA is known to strongly induce complement-dependent cytotoxicity, OBI is described to be far less efficient. In contrast, the role of complement in RTX-induced B cell depletion is still under debate. Some of this dissent might come from the use of different in vitro systems for characterization of antibody effector functions. We therefore set out to systematically compare antibody as well as C1q binding and complement-activation by RTX, OFA and OBI on human B cell lines that differ in expression levels of CD20 and complement-regulatory proteins as well as human primary B cells. Applying real-time interaction analysis, we show that the overall strength of C1q binding to live target cells coated with antibodies positively correlated with the degree of bivalent binding for the antibodies to CD20. Kinetic analysis revealed that C1q exhibits two binding modes with distinct affinities and binding stabilities, with exact numbers varying both between antibodies and cell lines. Furthermore, complement-dependent cell killing by RTX and OBI was highly cell-line dependent, whereas the superior complement-dependent cytotoxicity by OFA was independent of the target B cells. All three antibodies were able to initiate deposition of C3b on the B cell surface, although to varying extent. This suggests that complement activation occurs but might not necessarily lead to induction of complement-dependent cytotoxicity. This activation could, however, initiate complement-dependent phagocytosis as an alternative mechanism of therapeutic B cell depletion.
CRIS-Team Scopus Importer:2021-02-05
Keywords: B cells; C1q; CD20; CDC; interaction; Obinutuzumab; Ofatumumab; Rituximab

Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Impact of Plasma Membrane Domains on IgG Fc Receptor Function - Kara, Sibel; Amon, Lukas; Lühr, Jennifer; Nimmerjahn, Falk; Dudziak, Diana; Lux, Anja (Frontiers in Immunology, 2020)
Lipid cell membranes not only represent the physical boundaries of cells. They also actively participate in many cellular processes. This contribution is facilitated by highly complex mixtures of different lipids and incorporation of various membrane proteins. One group of membrane-associated receptors are Fc receptors (FcRs). These cell-surface receptors are crucial for the activity of most immune cells as they bind immunoglobulins such as immunoglobulin G (IgG). Based on distinct mechanisms of IgG binding, two classes of Fc receptors are now recognized: the canonical type I FcγRs and select C-type lectin receptors newly referred to as type II FcRs. Upon IgG immune complex induced cross-linking, these receptors are known to induce a multitude of cellular effector responses in a cell-type dependent manner, including internalization, antigen processing, and presentation as well as production of cytokines. The response is also determined by specific intracellular signaling domains, allowing FcRs to either positively or negatively modulate immune cell activity. Expression of cell-type specific combinations and numbers of receptors therefore ultimately sets a threshold for induction of effector responses. Mechanistically, receptor cross-linking and localization to lipid rafts, i.e., organized membrane microdomains enriched in intracellular signaling proteins, were proposed as major determinants of initial FcR activation. Given that immune cell membranes might also vary in their lipid compositions, it is reasonable to speculate, that the cell membrane and especially lipid rafts serve as an additional regulator of FcR activity. In this article, we aim to summarize the current knowledge on the interplay of lipid rafts and IgG binding FcRs with a focus on the plasma membrane composition and receptor localization in immune cells, the proposed mechanisms underlying this localization and consequences for FcR function with respect to their immunoregulatory capacity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cell membrane; CLR; FcγR; lipid rafts; membrane; membrane localization; type I FcR; type II FcR